Penguatan Ekosistem Usaha Maggot melalui Inovasi Teknologi, Edukasi Pengelolaan Sampah dan Pendampingan Digital - prihatin oktivasari (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2026)
Purpose –This community service aims to increase maggot production through innovative Internet of Things (IoT) based monitoring systems and post-harvest maggot processing using chopping machines and maggot drying machines. Design/methodology/approach – The method used in this community service program consists of the socialization stage, training stage, and mentoring stage for Maggot cultivator partners. Findings – Implementation of this technology can increase production efficiency, harvest quality, and selling value of dried maggot products, thereby helping to reduce waste and improve the economy of maggot cultivators. Partners understand the process of digital product marketing via social media and obtain a Business Identification Number (NIB). Originality/value –This community service program has never been carried out with program partners, so it focuses on the field of machine training and information technology as well as the field of digital marketing.